An adventure in statistics : the reality enigma - Field, Andy P.; Iles, James (Los Angeles : SAGE, 2016)
Providing a vibrant alternative to the dullness of many typical offerings, the book assumes no previous statistics knowledge nor does it require the use of data analysis software. It covers the material you would expect for an introductory level statistics course and presents strong foundations for understanding classical and Bayesian approaches to data analysis. Illustrated with stunning graphic-novel style art and featuring Socratic dialogue, the story captivates readers as it introduces them to concepts, eliminating potential statistics anxiety.
How to use this book -- Prologue: the dying stars -- Why you need science -- Reporting research, variables and measurement -- Summarizing data -- Fitting models [central tendency] -- Presenting data -- Z-scores -- Probability -- Inferential statistics: going beyond the data -- Robust estimation -- Hypothesis testing -- Modern approaches to theory testing -- Assumptions -- Relationships -- The general linear model -- Comparing two means -- Comparing several means -- Factorial designs -- Epilogue: the genial night -- Appendix -- Glossary -- References -- Index -- Acknowledgements.
Includes bibliographical references (pages 727-732) and index.
Keywords: Statistics -- Textbooks; Textbooks